The Mandate to Provide Expanded Core Curriculum Instruction. (May 2022) - Chase, Alan Anthony
Introduction: This study examined potential legal precedent set by holdings in administrative due process hearings where instruction in the expanded core curriculum (ECC) for school-age children was decided.Methods: This study used an analogical reasoning approach. This legal research method includes examining the rule of law, presenting cases for comparison, and applying the fact pattern to predict outcomes of current or future cases.Results: The results demonstrate that the inclusion of the ECC in an Individualized Education Program (IEP) varies from state to state. Only two states have passed legislation requiring instruction in the ECC. These statutes have been referenced in case holdings. Administrative hearings from four different jurisdictions in the United States have held that the ECC must be included in the IEP to some extent. Discussion: The ECC is a critical component of the education of students with visual impairments and must be incorporated in some form within their IEPs. Depending upon the jurisdiction, the ECC may have to be explicitly stated in the IEP, while in other locales it may have to be embedded within the IEP. In some states, specific statutes governing instruction in the ECC form the rule of law.Implications for Practitioners: School administrators and teachers of students with visual impairments should be knowledgeable of the legislation governing the ECC in their state and the legal precedents that have been created in their state. School administrators and teachers of students with visual impairments should carefully consider how the principles of a legal precedent can be applied to situations within their own communities to understand their obligations and likelihood of prevailing in any legal dispute. Finally, parents and students with visual impairments should be aware of the legal precedent created for the ECC in their state and use the dispute resolution process to inform change in their own communities as the families did in these exemplar cases.